A WINDOW INTO PAPUA’S PAST: ARCHAEOLOGICAL AND ANTHROPOLOGICAL STATUS QUO IN THE STAR MOUNTAINS [Melihat Masa Lalu Papua : Penelitian Arkeologi dan Antropologi di Pegunungan Bintang] - Schiefenhovel, Wulf; Vanhaeren, Marian (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2017)
In this paper, which is based on anthropological fieldwork in the Province of Papua, and literature research in archaeology and anthropology, we attempt to give an overview over the present status of research in Tanah Papua, with special focus on the prehistory and anthropology of groups in the interior, especially on the little known “Ok-Mek Minisphere” as well as on the potential routes of prehistoric migration to New Guinea and into the Star Mountains.  ABSTRAKTulisan didasarkan pada penelitian lapangan antropologi di Papua, dan penelitian kepustakaan arkeologi dan antropologi. Dalam penelitian ini mencoba untuk memberikan gambaran mengenai perkembangan penelitian saat ini di Papua, dengan fokus pada prasejarah dan antropologi di pedalaman, terutama di wilayah “Ok- Mek” yang sangat potensial sebagai jalur migrasi prasejarah ke New Guinea dan masuk ke Pegunungan Bintang.